Letter from G. W. Hunter to James Curtis Booth - Hunter, G. W. (1862)
G. W. Hunter, Secretary of the Academy of the Protestant Episcopal Church, informs James Curtis Booth (1810-1888) that he has been unanimously elected a Trustee of the Academy.
Keywords: Booth, James Curtis, 1810-1888; Academy of the Protestant Episcopal Church in the City of Philadelphia; Trusts and trustees